Pengaruh Keunikan Produk, Promosi dan Harga terhadap Keputusan Pembelian Minuman Kekinian Es Teler Ngombe 86 Argopuro - Wendi Wendi; Dassucik Dassucik; Ahmad Hafas Rasyidi (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2025)
This study aims to analyze the influence of product uniqueness, promotion, and price on purchasing decisions for contemporary beverages. Contemporary beverages are currently experiencing rapid development in line with changes in lifestyle and consumer preferences, requiring businesses to understand the factors that influence purchasing decisions. The research approach used was quantitative. The sampling technique used non-probability sampling with a purposive sampling method, with a sample size of 100 respondents, who were consumers of contemporary beverages. Data were collected through a questionnaire measured using a Likert scale. The data were then analyzed using SPSS version 23 using multiple linear regression analysis. The results showed that product uniqueness had no effect on purchasing decisions, nor did promotion. Meanwhile, price was shown to have a significant effect on purchasing decisions for contemporary beverages. This finding indicates that consumers prioritize the appropriateness of price to the benefits received over uniqueness and promotion. Therefore, businesses are expected to establish competitive pricing strategies while still considering uniqueness and promotion aspects to attract consumers.